Detection of Naegleria species in environmental samples from Peninsular Malaysia. - Init Ithoi (Public Library of Science (PLoS), 2011)
Background In Malaysia, researchers and medical practitioners are unfamiliar with Naegleria infections. Thus little is known about the existence of pathogenic Naegleria fowleri, and the resultant primary amoebic meningoencephalitis (PAM) is seldom included in the differential diagnosis of central nervous system infections. This study was conducted to detect the presence of Naegleria species in various environmental samples. Methods/findings A total of 41 Naegleria-like isolates were isolated from water and dust samples. All these isolates were subjected to PCR using two primer sets designed from the ITS1-ITS2 regions. The N. fowleri species-specific primer set failed to produce the expected amplicon. The Naegleria genus-specific primers produced amplicons of 408 bp (35), 450 bp (2), 457 bp (2) or 381 bp (2) from all 41 isolates isolated from aquatic (33) and dust (8) samples. Analysis of the sequences from 10 representative isolates revealed that amplicons with fragments 408, 450 and 457 bp showed homology with non-pathogenic Naegleria species, and 381 bp showed homology with Vahlkampfia species. These results concurred with the morphological observation that all 39 isolates which exhibited flagella were Naegleria, while 2 isolates (AC7, JN034055 and AC8, JN034056) that did not exhibit flagella were Vahlkampfia species. Conclusion To date, pathogenic species of N. fowleri have not been isolated from Malaysia. All 39 isolates that produced amplicons (408, 450 and 457 bp) from the genus-specific primers were identified as being similar to nonpathogenic Naegleria. Amplicon 408 bp from 5 representative isolates showed 100% and 99.7% identity to Naegleria philippinensis isolate RJTM (AM167890) and is thus believed to be the most common species in our environment. Amplicons 450 bp and 457 bp were respectively believed to be from 2 new species of Naegleria, since representative isolates showed lower homology and had a longer base pair length when compared to the reference species in the Genbank, Naegleria schusteri (AJ566626) and Naegleria laresi (AJ566630), respectively.